Exosomes from donor‐derived adipose mesenchymal stem cells prolong the survival of vascularized composite allografts. Issue 8 (16th January 2021) - Chen, Zhizhao; Xue, Shuai; Zhang, Sheng; Cheng, Ke; Ye, Qifa
Abstract: Donor‐derived adipose‐derived mesenchymal stem cells (ADMSCs) dampen the alloimmune response and exosomes are reported to have biological activity similar to their parent cells. Here, we investigated the roles of exosomes from donor‐derived ADMSCs (ADMSC‐exo) in vascularized composite allotransplantation (VCA). Brown Norway‐to‐Lewis rat hindlimb transplantations were intravenously treated with either exosome from donor‐derived ADMSCs or phosphate‐buffered saline, combined with a short course of immunosuppression. We established that the treatment with ADMSC‐exo prolongs the survival time of VCA grafts. Skin and muscle samples from ADMSC‐exo‐treated animals showed no histological signs of rejection, but samples from controls showed rejection of degree III. Comparing to the control group, a significant increase of donor cell chimerism, Tr1 and Treg, while a decrease of CD4 + T and Th1 cells were observed in the ADMSC‐exo‐treated group. Our findings imply that ADMSC‐exo may be a valuable and safe treatment for extending VCA graft survival. Abstract : 1. We first investigated the roles of exosomes from donor‐derived ADMSCs (ADMSC‐exo) in vascularized composite allotransplantation (VCA). 2. ADMSC‐exo prolongs the VCA graft survival by upregulation of donor cell chimerism, Tr1, and Treg, while downregulation of CD4 + T and Th1 cells.